Association Between Serum Furin and Fasting Glucose: A Cross-Sectional Study in Chinese Adults - He, Yan; Zhu, Hanyun; Zhang, Min; Li, Jing; Ma, Shengqi; Lu, Yin; Chen, Linan; Zhang, Mingzhi; Peng, Hao (Frontiers in Endocrinology, 2022)
Background: Furin has been associated with glucose metabolic phenotypes in small sampled clinical studies. However, this association has not yet been studied in Chinese. Here, we aimed to examine the association between serum furin and fasting glucose in Chinese adults. Methods: Serum furin and fasting plasma glucose were assayed for 2,172 participants (mean aged 53 years, 38% men) in the Gusu cohort. A median regression model was applied to examine the association between serum furin and fasting glucose, adjusting for age, sex, education level, cigarette smoking, alcohol drinking, obesity, blood pressure, and lipids. To facilitate data interpretation, the association between serum furin and prevalent diabetes was also examined. Results: Serum furin was negatively associated with fasting glucose (β=-0.18, P<0.001 for log-furin). In participants with diabetes, serum furin was significantly lower than those with normal glucose (median: 0.90 ng/mL vs. 1.05 ng/mL, P=0.001). Compared with participants in the highest quartile of serum furin, those in the lowest quartile had 42% and 80% increased risk of prevalent prediabetes (OR=1.42, 95%CI: 1.05-1.92, P=0.023) and diabetes (OR=1.80, 95%CI: 1.13-2.91, P=0.015), respectively. Conclusions: Serum furin was negatively associated with prediabetes and diabetes in Chinese adults. Our findings suggest that serum furin may be a risk factor or a biomarker of diabetes.